MiR-221 alleviates the inflammatory response and cell apoptosis of neuronal cell through targeting TNFAIP2 in spinal cord ischemia–reperfusion. Issue 8 (23rd May 2018) - Zhao, Dong; Deng, Shu-Cai; Ma, Yi; Hao, Yong-Hong; Jia, Zhan-Hua
Abstract : This study aimed to examine the role of miR-221 in inflammatory response and apoptosis of neuronal cells after spinal cord ischemia/reperfusion (I/R) injury. Blood samples were obtained from 20 I/R patients and that of 20 healthy individuals were used as a control. AGE1.HN and SY-SH-5Y neuronal cell lines subjected to oxygen–glucose deprivation (OGD) stress were used in cell experiments. Real-time PCR and western blot were used to evaluate the expression of miR-221, tumor necrosis factor-α, and TNFAIP2. TUNEL assay analyzed cell apoptosis. I/R patients had lower serum levels of miR-221 than healthy controls. In OGD-AGE1.HN and SY-SH-5Y cells, miR-221 was significantly downregulated and TNFAIP2 mRNA and protein were upregulated; meanwhile, both proinflammatory cytokine tumor necrosis factor-α and anti-inflammation cytokine interleukin-6 were elevated and the percentage of apoptotic cells was increased. This inflammatory response and cell apoptosis induced by OGD stress were attenuated by miR-221 overexpression and enhanced by miR-221 knockdown. TNFAIP2 is a target gene for miR-221 and could be regulated negatively by the miR-221 mimic or the miR-221 inhibitor with or without OGD stress. Accordingly, TNFAIP2 overexpression reversed the inflammatory response and cell apoptosis induced by miR-221 under OGD stress. Downregulation of miR-221 occurs in spinal cord I/R injury and in cell lines subjected to oxygen–glucose deprivation. miR-221 regulates the inflammatory response and apoptosis of neuronal cells through its impact on TNFAIP2.